Perancangan Antarmuka Dengan Metode User Centered Design Dan Prinsip WCAG 2.2 Pada Mata Pelajaran Matematika Kelas 2 (Studi Kasus: SLB-B Negeri Karya Mulia Surabaya) - Siti Nur Hamidah; Berlian Maulidya Izzati (CV. SINAR HOWUHOWU, 2026)
This research is motivated by the challenges faced by 2nd-grade deaf students at SLB-B Negeri Karya Mulia Surabaya in understanding basic mathematical concepts due to abstract verbal explanations. Their reliance on visual information processing highlights the need for a digital educational platform specifically designed to suit their cognitive abilities. The purpose of this study is to design an accessible and inclusive user interface (UI) for a mathematics educational website. The design approach applies the User Centered Design (UCD) method to focus on the user, while adhering to the Web Content Accessibility Guidelines (WCAG) 2.2 standards. In this document, the research scope is limited from the problem identification stage to the preliminary design, or wireframe, stage. Data collection was conducted through observations and interviews with educators to map the characteristics and user requirements of the deaf students. Based on this identification, a design solution was developed in the form of wireframes, which prioritize visual information delivery using colors, interactive icons, and text, without the use of audio elements. The wireframe output includes interface designs for the Login, Home, Material, Quiz, Quiz Results, and Profile pages, which are intended to serve as the foundation for subsequent system prototype development.